Análise da influência do uso de telas no cultivo de uvas da espécie “Benitaka” (Vitis vinífera) no município de Capão Bonito – SP - Bernardo, Taynara Aparecida (Universidade Federal de São Carlos, 2021)
The objective of this study was to evaluate the influence of microclimatic changes, through the use of different shading screens colors on the vegetative and productive response under the climatic conditions of the city of Capão Bonito - SP. Benitaka vineyards (Vitis vinifera) of the area in full sun (without coverage) and covered with shading screens in red, black and aluminized colors were used. The analysis was separated in two moments: microclimate analysis and plant analysis. For the analysis of the microclimate effect, the multiparameter equipment was used to take measurements of light, air temperature and relative humidity, where the sensors were positioned above the usable vine and below the metalic structure during the period from 12h to 13h. For the plant analysis, the leaves of the vines and the quality of the fruit were analyzed. For the leaf analysis, the software ImageJ® was used to obtain data on leaf length and leaf area. In order to analyze the fruit harvested four bunches of grapes in the different treatments according to their maturity, these were weighed using a digital scale in order to obtain the weight of clusters, using a ruler and a plate with a white background took the measurements of width and height of the clusters. For the analysis of the sugar content used a reflatometer, selected from the bunches of grapes three berries from different locations being, top, middle and bottom, being macerated to obtain the liquid that determines the content of soluble solids. It was analyzed that the screens showed significant interference in modifying the microclimate under the screens and in the productivity of the crop. In relation to the microclimate, the luminousity variable showed better results under the control screen compared to the shading screens, and in comparison between the screens, the red colored screen showed better results. The air temperature showed higher values under the red fabric compared to the control and other fabrics, showing that it can be used in periods of mild air temperature, preventing frost loss. Another factor, relative humidity, knowing that mildew is the main fungal disease of the grapevine and its propagation occurs in environments with high relative humidity and air temperature, it was observed that the red cloth showed lower values compared to the other screens. The production and quality of the grapevine were measured by the variables soluble solids content (brix), bunch weight (g), production per plant (g), number of bunches, height and width of bunches, where the red shade cloth stood out in relation to sugar content and production per plant; the black shade cloth in the weight and height of the bunch, the aluminized screen in relation to the width of the bunch and the open air screen in the number of bunches.
Analysis of the influence in use of shadow nets applied to the growing “Benitaka” grape species (Vitis vinífera) in Capão Bonito city - SP
Keywords: Tela de sombreamento; Microclima; Produtividade; Qualidade; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::ENGENHARIA AGRICOLA::CONSTRUCOES RURAIS E AMBIENCIA